A comparison of correlates associated with adult physical activity behavior in major cities and regional settings - Short, C.; Vandelanotte, C.; Rebar, Amanda; Duncan, M. (American Psychological Association, 2014)
© 2013 American Psychological Association. Objective: People living outside of urban areas are at higher risk for physical inactivity. Understanding physical activity correlates in different settings is important for understanding this risk. This study compared psychological, demographic, and health-related correlates of activity among adults living in major cities (urban areas) and regional (low-population density) towns and whether there were significant differences in how these potential determinants related to physical activity. Methods: Participants (n = 756) were male and female adults who were members of the Australian Health and Social Science panel. Participant characteristics and physical activity were assessed using standardized measures via an online survey. Differences in the strength of the relation between the physical activity correlates were tested using equality of regression coefficient tests. Results: Few differences in physical activity determinants between major cities and regional settings were observed. For major city and regional areas, self-efficacy and outcome expectations were the most strongly related correlates to physical activity. The strength of associations between the correlates and physical activity did not differ between areas, with the exception of working status. Not working was associated with lower odds of meeting physical activity guidelines for major city residents but not for regional residents. Conclusion: Physical activity correlates were generally similar for people living in major city and regional areas. This suggests that physical activity interventions targeting personal factors do not need to tailor to a person's level of urbanization. Studies examining the interaction between psychological correlates of physical activity and environmental factors are needed.